2016
DOI: 10.1371/journal.pone.0159076
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenic Protein RodZ Interacts with Sporulation Specific SpoIIE in Bacillus subtilis

Abstract: The first landmark in sporulation of Bacillus subtilis is the formation of an asymmetric septum followed by selective activation of the transcription factor σF in the resulting smaller cell. How the morphological transformations that occur during sporulation are coupled to cell-specific activation of transcription is largely unknown. The membrane protein SpoIIE is a constituent of the asymmetric sporulation septum and is a crucial determinant of σF activation. Here we report that the morphogenic protein, RodZ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 59 publications
(81 reference statements)
1
32
0
Order By: Relevance
“…The literature suggests that SpoIIE may regulate cell wall synthesis at the asymmetric division sites (Piggot and Coote, 1976; Illing and Errington, 1991; Barák and Youngman, 1996) and may play a role in peptidoglycan remodeling during engulfment (Campo et al, 2008). Indeed, a recent study indicated that SpoIIE recruits the morphogenic protein RodZ at the asymmetric septum during sporulation where both proteins might be involved in peptidoglycan thinning during engulfment (Muchova et al, 2016). The second distinct function of SpoIIE during sporulation is the activation of σ F in the forespore due to its phosphatase activity (Duncan et al, 1995; Arigoni et al, 1996; Feucht et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…The literature suggests that SpoIIE may regulate cell wall synthesis at the asymmetric division sites (Piggot and Coote, 1976; Illing and Errington, 1991; Barák and Youngman, 1996) and may play a role in peptidoglycan remodeling during engulfment (Campo et al, 2008). Indeed, a recent study indicated that SpoIIE recruits the morphogenic protein RodZ at the asymmetric septum during sporulation where both proteins might be involved in peptidoglycan thinning during engulfment (Muchova et al, 2016). The second distinct function of SpoIIE during sporulation is the activation of σ F in the forespore due to its phosphatase activity (Duncan et al, 1995; Arigoni et al, 1996; Feucht et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…This observation supports a model in which SpoIIE interacts with other proteins or complexes. In stage II i interactions would be with components of the divisome (12)(13)(14) while in stage II iii they would be with SpoIIQ, the forespore component of an intercellular channel formed with proteins encoded on the spoIIIA operon expressed in the mother cell (15).…”
Section: Spoiie Mobility Depends On Stagementioning
confidence: 99%
“…Gene cloning in B. subtilis, unless specified, was performed using standard protocols (53) ( Table S1). To construct pSGIIE-mGFP, we used previously prepared pSGIIE-YPet (13). A PCR fragment containing mGFP was prepared using mGFPKpnF: (53) supplemented with chloramphenicol (5µg ml -1 ), erythromycin (1µg ml -1 ) and lincomycin (25µg ml -1 ) as required.…”
Section: Strains and Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations